Effect of glutamine and proline spraying on some qualitative and physiological characteristics of soft wheat genotypes. Triticum aestivum L. - Alaa S. Fadala; Faisal. M. Al-Tahir (Zien Journals, 2022)
A field experiment was carried out during the winter season of 2021 in one of the farmers’ fields (The al-Batira area is 20 km away from the center of Maysan Governorate) in soil with a silty loam soil texture to know the effect of spraying by glutamine and proline on some Qualitative and physiological traits of soft wheat genotypes (Triticum aestivum L.). The experiment was implemented in a split-plot method using a randomized complete block design (R.C.B.D) with three repetitions. The experiment included a study of two factors; the first was spraying by the amino acids glutamine and proline: the control treatment spraying only distilled water; The second treatment was sprayed by glutamine amino acid at a concentration of 300 mg l-1 ; the third treatment was sprayed amino acid proline at a concentration of 300 mg l-1 ; the fourth treatment was a mixture of amino acid gluten + proline at a concentration of 150 mg l-1 for each. The second factor includes ten newly introduced genotypes from soft wheat, which are as follows; (Russian V10, ACSAD 133, ADANE 99, ACSAD 59, ACSAD 901, Iranian, Wafiya, Jad (Germanian), Jihan, Bohouth22). Spraying was in two batches, the first at elongation and the second at the flowering stage. The studied traits are total tillers number of plants, plant dry weight (Mg ha-1 ), moisture percentage, a specific weight (kg ha1 ), ash content in grains (%), and flour protein percentage (%). The results were as follows: the cultivar plants outperformed it is Wafiya and gave the highest average of tillers number, which amounted to 436.39 m2 . The cultivar ACSAD 59 excelled in plant dry weight, giving the highest average dry weight of 9.2 Mg ha-1 ; also, the cultivar ACSAD 133 excelled in the moisture percentage at a rate of 10.79%. The study showed that the genotype ACSAD 901 gave the highest average specific weight of the grain, amounting to 76.87 (kg hec-1 ), while the genotype ACSAD133 was superior in terms of the percentage of ash in the grain and the percentage of protein in the grain, giving the highest averages of 1.13% and 12.05%. The study showed that the qualitative traits and the physiological could be improved by spraying the amino acids glutamine and proline, especially in the elongation and flowering stage. There was an improvement in the specific and physiological characteristics through spraying these acids and in such stages.
Keywords: physiological; flowering; improvement; highest